2018
DOI: 10.1128/aac.02637-17
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidative Stress and First-Line Antituberculosis Drug-Induced Hepatotoxicity

Abstract: Hepatotoxicity induced by antituberculosis drugs is a serious adverse reaction with significant morbidity and even, rarely, mortality. This form of toxicity potentially impacts the treatment outcome of tuberculosis in some patients. Covering only first-line antituberculosis drugs, this review addresses whether and how oxidative stress and, more broadly, disturbance in redox homeostasis alongside mitochondrial dysfunction may contribute to the hepatotoxicity induced by them. Risk factors for such toxicity that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 72 publications
1
47
0
4
Order By: Relevance
“…Additionally, plasma specimens collected at different time points during treatment from each patient are also important for ADR studies. Previous studies have shown that oxidative stress, and more broadly, disturbances in redox homeostasis alongside mitochondrial dysfunction, may contribute to the hepatotoxicity induced by first-line anti-TB drugs 49. A rat study suggested that INH may initiate its toxicity in liver mitochondria through interactions with electron transfer chains, lipid peroxidation, mitochondrial membrane potential decline and cytochrome c expulsion, which ultimately leads to cell death 50.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, plasma specimens collected at different time points during treatment from each patient are also important for ADR studies. Previous studies have shown that oxidative stress, and more broadly, disturbances in redox homeostasis alongside mitochondrial dysfunction, may contribute to the hepatotoxicity induced by first-line anti-TB drugs 49. A rat study suggested that INH may initiate its toxicity in liver mitochondria through interactions with electron transfer chains, lipid peroxidation, mitochondrial membrane potential decline and cytochrome c expulsion, which ultimately leads to cell death 50.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that INH could induce ROS levels and apoptosis in both HepG2 and THLE‐2 cells, and the expression of apoptotic and antioxidative genes was shown to increase . Experimental and clinical studies indicated that oxidative stress, resulting from abnormal ROS accumulation, plays an important role in ATLI …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…9 Experimental and clinical studies indicated that oxidative stress, resulting from abnormal ROS accumulation, plays an important role in ATLI. 10 Nuclear factor erythroid 2-related factor 2 (Nrf2) and its endogenous inhibitor kelch-like ECH associating protein 1 (Keap1) function as a ubiquitous, evolutionarily conserved intracellular defense mechanism to counteract oxidative stress. 11 Oxidative stress causes Nrf2 to detach from Keap1 and translocate to the nucleus, wherein it heterodimerizes with small musculoaponeurotic fibrosarcoma proteins.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…https://doi.org/10.1101/2020.04. 14.20065292 doi: medRxiv preprint for toxicity prevention 13 . Here, we hypothesized that long-term exposures to isoniazid and its metabolites were related to markers of redox imbalance in hepatocytes, and that hydrazine exposures would drive redox imbalance and oxidative damage in the liver.…”
Section: Introductionmentioning
confidence: 99%